Application of decision tree and relative proximity to evaluation of sustainable development capacities of listed electric power companies - Mou, Hao; Tang, Xiaobo; Gao, Hexuan; Liu, Yalan (Journal of Business Economics and Management, 2022)
In a complex market environment with fierce competition, maintaining their current market positions is an important issue for electric power companies. Sustainable development not only requires them to pay attention to their current operating efficiencies but also to actively participate in environmental and social responsibilities to maintain their competitive advantages. This paper proposes a model for evaluating the sustainable development capacities of power companies. Firstly, the preliminary evaluation indicator system is constructed with the seven dimensions of production safety, public relations and social welfare, shareholder rights protection, environmental sustainability, employee rights protection, scientific research innovation ability, and financial status. Then, specific financial indicators are selected by CART to avoid indicator redundancies and the final evaluation indicator system is constructed. Finally, the relative proximity calculated by the TOPSIS method is applied to evaluate the sustainable development capacities. An empirical study of 18 listed electric power companies is conducted to verify the evaluation model. The results show that the performances of these companies in production safety and environmental sustainability are generally satisfactory, but the overall performances in public relations and social welfare, employee rights protection, and scientific research innovation ability are relatively poor, so these dimensions should be strengthened.First published online 15 July 2022